Reformation Worlds Antecedents and Legacies in the Anglican Tradition - Otto, Sean A.; Otto, Sean A.; Power, Thomas P. (Peter Lang, 2016)
A reassessment of the precedents, course, and legacy of the Reformation has occurred in the present generation of academic writing. This collection of essays brings together research by established and new scholars on themes of the Reformation with a particular focus on its antecedents and legacies in the Anglican tradition. Utilizing a diversity of topics, approaches, and methods, this book adds measurably to our knowledge of the place of the Reformation in Britain and Ireland as well as its European, North American, and African particularities. Exploring a variety of themes, this collection examines the Reformation in relation to key aspects of church organization, belief, sacrament, conversion, relationships with other denominations, theological education, church and state, worship, and issues of resilience and decline. While these themes are pursued broadly, there is a particular focus on the context of the Anglican tradition in terms of Reformation preoccupations and concerns. This collection$1 (Bs thematic content, chronological span, and geographical range will also challenge accepted views, deepen understanding, and highlight new areas of enquiry, bringing new research and insights to bear on established observations. Academics will find this book of particular interest for courses on the Reformation, Early Modern Europe, and the history of Christianity.s